1999
DOI: 10.1165/ajrcmb.21.1.3511
|View full text |Cite
|
Sign up to set email alerts
|

Lung Growth Response after Tracheal Occlusion in Fetal Rabbits Is Gestational Age–Dependent

Abstract: In utero tracheal occlusion (TO) is a potent stimulus of fetal lung growth, and is currently being applied in clinical trials to treat severe forms of pulmonary hypoplasia. The aim of this study was to examine the effect of timing of TO on pulmonary growth and maturation rates. Fetal rabbits (term = 31 d) were subjected to in utero tracheal clipping at 24 (late pseudoglandular stage) or 27 d of gestation (late canalicular/early terminal sac stage). Sham-operated littermates served as controls (C). Animals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 24 publications
5
60
1
1
Order By: Relevance
“…Possibilities include species differences, the method of inducing pulmonary hypoplasia (oligohydramnios vs. spinal cord section), the magnitude of change in distension, and the relative maturity of the lungs (10,36). Previous investigators have shown that pulmonary surfactant in fetal rats is increased by both endogenous (45) and exogenous glucocorticoids (38).…”
Section: Discussionmentioning
confidence: 99%
“…Possibilities include species differences, the method of inducing pulmonary hypoplasia (oligohydramnios vs. spinal cord section), the magnitude of change in distension, and the relative maturity of the lungs (10,36). Previous investigators have shown that pulmonary surfactant in fetal rats is increased by both endogenous (45) and exogenous glucocorticoids (38).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei were stained with Hoechst. Results were expressed as the ratio of the pixel area of ␣-SMA staining (520 -530 nm) over the pixel area of the nuclei (15). Digital images were captured using the red channel to optimize contrast.…”
Section: Methodsmentioning
confidence: 99%
“…However, using three well-established methods to detect apoptosis (light and electron microscopy, the nucleosomal ladder pattern of DNA digestion, and the detection of apoptotic cells in situ by the terminal deoxynucleotidyl transferase-mediated nick-end labeling method), a shift in apoptosis was observed from the mesenchymal tissue layer during the earlier stages of development (9) to both the epithelial and mesenchymal tissue layers during the canalicular stage of development and onward (10,11). Increasing AEC2 apoptosis coincided with a decrease in cell proliferation, implicating epithelial apoptosis as a significant contributor of lung remodeling during late gestational development (12,13). Throughout the embryonic stage of lung development, apoptosis was almost exclusively found in the peripheral mesenchyme in regions of new bud formation or in the mesenchyme underlying branch points that are the site of extensive epithelial branching morphogenesis and remodeling of interstitial tissue, allowing room for outgrowth of the lung bud (10,14).…”
Section: Apoptosis and Lung Developmentmentioning
confidence: 96%